Improving Clinical Documentation Compliance Pre-Gastrointestinal Endoscopy Procedures Through the Use of an Endoscopy Checklist. (24th September 2022) - Kelly, Veronica; Baar-Daley, K. Michelle
Abstract : Production pressure in endoscopy units, to avoid procedural delays, can lead to documentation gaps that pose a patient safety risk. Fast-paced, high-volume endoscopy units within a 673-bed academic medical center, incomplete and illegible documentation were identified during a 2018 Joint Commission survey. Pre-procedure safety checklists help ensure accurate clinical handovers. Checklists promote team communication that includes the patient to have complete and relevant information to perform a safe procedure and speak up to identify discrepancies. An endoscopy-specific safety checklist was used by the procedural team immediately pre-procedure. This quality improvement project used Plan Do Study Act cycles to incorporate changes suggested by users. Chart audits were conducted pre- and post-pilot. The results showed significant improvements in physician documentation completeness and legibility, suggesting the checklist prompted clarification of documentation and communication between the nurse and the physician. Nursing assessment saw a 27.1% improvement, suggesting clarification of clinical handover between the admitting and procedural nurses. Improved communication was perceived by staff. This project showed how a standardized tool to promote team communication and clarification of discrepancies pre-procedure can contribute to prevention of errors.